О власти языка и языке власти - Лaссaн, Э. Р. (Kalbotyra, 1991)
The article discusses the peculiarities of the language style of the political processes in the period of 1930-1989. Analysis of the style permits to reveal the system of views, i.e. ideological stereotypes. The vocabulary of the power against the citizens of its country comes out. Linguistic means and psycholinguistic methods used by the power had an affect upon the minds and thinking of its citizens.